VALUABLE PUBLIC SPEAKING SKILLS FOR LEGAL PROFESSIONALS - Matei, Mădălina (Universitatea Transilvania Brasov, 2021)
In the constant endeavour to improve their public speaking skills, legal professionals must be aware of the main aspects that they have to control and of the framework that they may use for that purpose. The elements of oral communication, politeness strategies, persuasion strategies, the main coordinates of verbal and nonverbal communication are surveyed in this article with the purpose of setting a point of departure for people working in the legal field who want to master the art of public speaking in order to become more credible, more efficient and more successful in their professional field.
Keywords: public speaking; persuasion; credibility; communication.